2022
DOI: 10.1097/corr.0000000000002136
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Colonization With Staphylococcus Aureus in THA Is Associated With Increased Length of Stay

Abstract: BackgroundStaphylococcus aureus is a common organism implicated in prosthetic joint infection after THA and TKA, prompting preoperative culturing and decolonization to reduce infection rates. It is unknown whether colonization is associated with other noninfectious outcomes of THA or TKA.Questions/purposes(1) What is the association between preoperative S. aureus colonization (methicillin-sensitive S. aureus [MSSA] and methicillin-resistant S. aureus [MRSA]) and the noninfectious outcomes (discharge destinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The current study [14] is, to my knowledge, the first study to show a relationship between S. aureus colonization and increased LOS after THA and 90-day readmission after TKA, and so we need to determine whether these findings can be consistently replicated in other centers with other patient populations. As the authors point out, it is unlikely that there is a causal link between colonization and the short-term outcomes of arthroplasty, but colonization with S. aureus may serve as a proxy for patient factors that were not explored in the current study.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…The current study [14] is, to my knowledge, the first study to show a relationship between S. aureus colonization and increased LOS after THA and 90-day readmission after TKA, and so we need to determine whether these findings can be consistently replicated in other centers with other patient populations. As the authors point out, it is unlikely that there is a causal link between colonization and the short-term outcomes of arthroplasty, but colonization with S. aureus may serve as a proxy for patient factors that were not explored in the current study.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…We read your recent article “Preoperative Colonization With Staphylococcus Aureus in THA Is Associated With Increased Length of Stay” with great interest [10]. The study design and data collection were impressive, and the results were well presented.…”
mentioning
confidence: 99%
“…We thank CORR ® for allowing us the opportunity to respond to the letter by Drs. Harris and Hegde [4] on our recent article, “Preoperative Colonization With Staphylococcus Aureus in THA Is Associated With Increased Length of Stay” [7].…”
mentioning
confidence: 99%
“…First, we agree that S. aureus colonization is a well-established risk factor for surgical site infection after total hip and knee arthroplasty, and that decolonization has been previously demonstrated to be associated with decreased rates of surgical site infection. In this study, after controlling for all variables available at the time, we found that preoperative S. aureus colonization (whether with methicillin-sensitive or methicillin-resistant S. aureus ) was associated with increased length of stay (LOS) after THA and increased odds of readmission after TKA [7]. With this information available, we believe that there is always value in further discussing with patients their risk/benefit profiles, and in this setting, S. aureus colonization was associated with increased LOS after THA and 90-day readmission after TKA, despite preoperative decolonization.…”
mentioning
confidence: 99%